If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -8 + 4x = -16 Reorder the terms: -8 + 4x + 4x = -16 Combine like terms: 4x + 4x = 8x -8 + 8x = -16 Solving -8 + 8x = -16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 8x = -16 + 8 Combine like terms: -8 + 8 = 0 0 + 8x = -16 + 8 8x = -16 + 8 Combine like terms: -16 + 8 = -8 8x = -8 Divide each side by '8'. x = -1 Simplifying x = -1
| 3b-3=4b+9 | | -4x-4=36 | | 12x/12=35/12 | | 9=2r-3+6 | | 2x+1=x+111 | | 2x+7=2x+5 | | (3x+2y-1)dx=(2x-3y+1)dy | | -11/9x3/10 | | 8s-10=27-(3s-7) | | x+4+6x=-3 | | 3x+10x-(5x+9)= | | 1/3a-2=15 | | 2h+5k-h+3k+4h= | | 2x=10x+21 | | 7x+3(-5+3)=-71 | | c/-3-1-2 | | k+1+4=5 | | -5y+10=10y | | (4/3)+(x/5)=(3x-5/6) | | x/6-x/2=-6 | | (2x+7)(2x^2+4x+4)= | | -5(-2-3z)= | | -6(2x+1)=-3x+7-9x | | -3(2x+1)-5=10 | | 5(4r+2)=2(10r+5) | | 2x+8=4(x+6) | | 5s-2t+7s-9t= | | .3+4x=3x+6 | | -19(-4h-7k+5)= | | 6m-4+6m=-16 | | -3/5=y-1/2 | | (-9*6)+-4= |